2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2018
DOI: 10.1109/embc.2018.8513177
|View full text |Cite
|
Sign up to set email alerts
|

Single Locked Nucleic Acid-enhanced nanopore genetic discrimination of pathogenic serotypes and cancer driver mutations

Abstract: Accurate and rapid detection of single-nucleotide polymorphism (SNP) in pathogenic mutants is crucial for many fields such as food safety regulation and disease diagnostics. Current detection methods involve laborious sample preparations and expensive characterizations. Here, we investigated a single locked nucleic acid (LNA) approach, facilitated by a nanopore singlemolecule sensor, to accurately determine SNPs for detection of Shiga toxin producing Escherichia coli (STEC) serotype O157:H7, and cancer-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…These assays involve minimal losses of target molecules during sample preparation while at the same time protecting the nanopore by the selective degradation of background molecules. For example, a biological nanopore-based direct, digital counting of single-nucleotide polymorphic sites marked with locked nucleic acid-synthetic molecules was used for the detection of Shiga toxin-producing Escherichia coli serotype and cancer-derived driver mutations 35,124 . Another approach using solid-state nanopores capitalized on the extremely high specificity of DNA ligase to pull down selected circulating tumour DNA mutations associated with breast cancer genes (that is, ERBB2 and PIK3Ca) in blood samples 34 .…”
Section: Biomarker Identification and Quantification Using Nanoporesmentioning
confidence: 99%
“…These assays involve minimal losses of target molecules during sample preparation while at the same time protecting the nanopore by the selective degradation of background molecules. For example, a biological nanopore-based direct, digital counting of single-nucleotide polymorphic sites marked with locked nucleic acid-synthetic molecules was used for the detection of Shiga toxin-producing Escherichia coli serotype and cancer-derived driver mutations 35,124 . Another approach using solid-state nanopores capitalized on the extremely high specificity of DNA ligase to pull down selected circulating tumour DNA mutations associated with breast cancer genes (that is, ERBB2 and PIK3Ca) in blood samples 34 .…”
Section: Biomarker Identification and Quantification Using Nanoporesmentioning
confidence: 99%
“…246 Moreover, it has been demonstrated that incorporation of α-L-LNA into DNAzymes can markedly enhanced DNAzyme activity, and recently, LNA proved efficient for detection of single-nucleotide polymorphisms using nanopore technology. 247,248 Likewise, the use of LNA nucleotides proved crucial to Mirkin and co-workers for the creation of superlattices from oligonucleotide-modified gold nanoparticles (AuNPs) of various well-defined shapes. 249 Incorporation of LNA into DNA nanostructures provides a straightforward route to fine-tuning and optimizing nanostructure function.…”
Section: Locked Nucleic Acid (Lna)mentioning
confidence: 99%
“…STEC is naturally found in the microbiota of ruminants, which are the most important reservoirs of this zoonotic pathogen (Ballem et al, 2020). Additionally, E. coli O157:H7 is the most important and frequently -978-90-04-51729-5 Downloaded from Brill.com02/13/2023 03:31:30AM via free access isolated serotype of STEC (Siddiqui & Yuan, 2021;Tian et al, 2018). Moreover, the low infectious dose of E. coli O157:H7 may be one of the factors why this serotype is involved in many outbreaks.…”
Section: Escherichia Colimentioning
confidence: 99%